PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) THAILAND DALAM MENANGANI KASUS TINDAK PIDANA PERDAGANGAN ORANG DI PERBATASAN THAILAND-MYANMAR TAHUN 2022 - Indarto, Indarto (TRANSBORDERS: International Relations Journal, 2023)
Abstract Using the theory of the role of international organizations, this research explains how the role of the International Organization for Migration (IOM) Thailand handles cases of Trafficking in Person (TIP) on the Thailand-Myanmar border in 2022. First, the role of the instrument, IOM Thailand helps the Thai government through the The Promise II program which helps Prospective migrant workers from Myanmar receive appropriate qualifications. Second, the role of the arena, IOM Thailand supports international forums discussing human trafficking crimes through the Bali Process forum, Coordinated Mekong Ministerial Initiative Against Trafficking (Commit Process). Third, the role of independent actors, IOM Thailand implements the 4P strategy to handle the crime of human trafficking. The results of this research show that IOM Thailand has fulfilled the criteria for its role as an international organization in handling human trafficking cases. Keywords: IOM Thailand; Trafficking in Persons (TIP); Thailand-Myanmar; The Promise II. Abstrak Menggunakan teori peran organisasi internasional, penelitian ini menjelaskan bagaimana peran International Organization for Migration (IOM) Thailand menangani kasus Tindak Pidana Perdagangan Orang (TPPO) di perbatasan Thailand-Myanmar tahun 2022. Pertama, peran instrument, IOM Thailand membantu pemerintah Thailand melalui program The Promise II yang membantu para calon pekerja migran asal Myanmar mendapat kualifikasi layak . Kedua, peran arena, IOM Thailand mendukung forum internasional membahas kejahatan perdagangan manusia melalui forum Bali Procces, Coordinated Mekong Ministerial Initiative Againts Trafficking (Commit Process),. Ketiga, peran independent actor, IOM Thailand menerapkan strategi 4P menangani Tindak Pidana Perdagangan Orang. Hasil penelitian ini menunjukkan IOM Thailand sudah memenuhi kriteria peran sebagai organisasi internasional dalam menangani kasus Tindak Pidana Perdagangan Orang. Kata Kunci: IOM Thailand; Tindak Pidana Perdagangan Orang (TPPO); Thailand-Myanmar; The Promise II.